Contribution to the characterization and modeling of photovoltaic generators - Angulo Abanto, Jose Ruben (Pontificia Universidad Católica del Perú, 2023)
A crucial aspect of evaluating and maintaining a photovoltaic (PV) installation connected to the grid is the availability of models that describe its operation reliably in real operating conditions. The nominal power of the PV generator (P*M) is considered an essential input parameter, and several models have been proposed to estimate P*M for characterizing the PV system. In the case of PV generators in outdoor conditions, the American Society for Testing and Materials, the International Electrotechnical Commission, and others have proposed procedures to determine the P*M of the generator. As part of these procedures, monitoring days with ideal conditions is mandatory, notably days with a clear sky, high irradiance values, and low wind speeds. Such restrictions can limit the number of suitable monitoring days, especially in places where clouds frequently form. This thesis proposes a new approach that allows estimating the P*M with data even from non-ideal, partially cloudy days. Based on non-parametric statistics, this procedure identifies and filters out noise as well as deviations from ideal conditions of irradiance, allowing for an estimation of P*M with similar accuracy as for a clear-sky day. This new procedure enables the characterization of a PV generator on a daily basis without the requirement to meet ideal conditions, thus, considerably enhancing the number of suitable monitoring days. To overcome the limitation in the P*M estimation and considerably extend the number of monitoring days, the new procedure can be applied to ideal and non-ideal conditions, such as partially cloudy days. This procedure determines the most probable nominal power value within one monitoring day using non-parametric statistics. In order to test the new procedure, a 109.44 kW photovoltaic plant in Granada, Spain, was monitored for six months. A referential procedure reported in the literature for large PV plants under ideal climatic conditions is first applied to estimate its nominal power. The results indicate that the nominal power can be estimated reliably in non-ideal conditions, maintaining the same precision as in ideal conditions. Then validating the procedure for a smaller PV generator and under different conditions, two small grid-connected 1.5 kW PV arrays were used. The PV systems in question are located in two different cities in Peru: Chachapoyas (tropical highland) and Lima (coastal desert). The objective of this study in Chachapoyas was to validate the methodology in a tropical climate with a high presence of clouds but at the same time with high irradiance values above 800 W/m2. According to the results obtained, under these conditions, the nominal power of the system can be calculated with reasonable certainty. As a precaution, monitoring for more than one day is recommended to obtain more data (at least 3 hours with high irradiance) to reduce uncertainties. Lima, Peru's second location under study, has a particular climate. Since the capital is located in a desert with high relative humidity values, dust deposition increases and power output decreases due to these conditions. For this purpose, the nominal power was used as a parameter to determine the maintenance schedule. Since keeping the system in optimal performance, considering this in future installations for operation and maintenance costs, is essential. The new procedure developed in this work can be applied to facilitate technical due diligence and quality control processes for PV generators of different sizes and under different operating conditions that are being re-purchased or have been recently installed. The possibility of daily monitoring of the P*M also enables long-term monitoring of a PV generator to ensure the correct operation or identify possible degradation effects

Un aspecto crucial a la hora de evaluar y mantener una instalacion fotovoltaica (FV) conectada a la red es la disponibilidad de modelos que describan su funcionamiento de forma fiable en condiciones reales de funcionamiento. La potencia nominal del generador fotovoltaico (P*M ) se considera un parametro de entrada esencial y se han propuesto varios modelos para estimar P*M para caracterizar el sistema fotovoltaico. En el caso de generadores fotovoltaicos en condiciones exteriores, la Sociedad Estadounidense de Pruebas y Materiales (abreviatura del ingles ASTM), la Comision Electrotecnica Internacional (abreviatura del ingles IEC) y otros han propuesto procedimientos para determinar la P*M del generador. Como parte de estos procedimientos, es obligatorio monitorear los dias con condiciones ideales, en particular los dias con cielo despejado, valores de irradiancia altos y velocidades de viento bajas. Tales restricciones pueden limitar la cantidad de dias de monitoreo adecuados, especialmente en lugares donde se forman nubes con frecuencia. Esta tesis propone un nuevo enfoque que permite estimar la P*M con datos incluso de dias parcialmente nublados no ideales. Basado en estadistica no parametricas, este procedimiento identifica y filtra el ruido, asi como las desviaciones de las condiciones ideales de irradiancia, lo que permite una estimacion de P*M con una precision similar a la de un dia de cielo despejado. Este nuevo procedimiento permite la caracterizacion diaria de un generador fotovoltaico sin el requisito de cumplir con las condiciones ideales, lo que aumenta considerablemente el numero de dias de monitoreo adecuados. Para superar la limitacion en la estimacion de P*M y extender considerablemente el numero de dias de monitoreo, el nuevo procedimiento se puede aplicar a condiciones ideales y no ideales, como dias parcialmente nublados. Este procedimiento determina el valor de potencia nominal mas probable dentro de un dia de monitoreo utilizando estadisticas no parametricas. Para probar el nuevo procedimiento, se monitorizo durante seis meses una planta fotovoltaica de 109,44 kW en Granada, Espana. Primero se aplica un procedimiento referencial reportado en la literatura para grandes plantas fotovoltaicas en condiciones climaticas ideales para estimar su potencia nominal. Los resultados indican que la potencia nominal se puede estimar de forma fiable en condiciones no ideales, manteniendo la misma precision que en condiciones ideales. Luego, para validar el procedimiento para un generador fotovoltaico mas pequeno y en diferentes condiciones, se utilizaron dos pequenos generador fotovoltaicos de 1,5 kW conectados a la red. Los sistemas fotovoltaicos en cuestion estan ubicados en dos ciudades diferentes de Peru: Chachapoyas (altiplano tropical) y Lima (desierto costero). El objetivo de este estudio en Chachapoyas fue validar la metodologia en un clima tropical con alta presencia de nubes pero al mismo tiempo con altos valores de irradiancia por encima de 800 W/m2. De acuerdo con los resultados obtenidos, en estas condiciones se puede calcular con razonable certeza la potencia nominal del sistema. Como precaucion, se recomienda monitorear durante mas de un dia para obtener mas datos (al menos 3 horas con alta irradiacion) para reducir las incertidumbres. Lima, la segunda localidad del Peru bajo estudio, tiene un clima particular. Dado que la capital esta ubicada en un desierto con altos valores de humedad relativa, la deposicion de polvo aumenta y la produccion de energia disminuye debido a estas condiciones. Para ello, se utilizo la potencia nominal como parametro para determinar el programa de mantenimiento. Ya que mantener el VI sistema en un desempeno optimo, considerando esto en futuras instalaciones para costos de operacion y mantenimiento, es fundamental. El nuevo procedimiento desarrollado en este trabajo se puede aplicar para facilitar los procesos de diligencia debida tecnica y control de calidad para generadores fotovoltaicos de diferentes tamaños y en diferentes condiciones de funcionamiento que se están recomprando o que se han instalado recientemente. La posibilidad de monitorear diariamente la P*M también permite monitorear a largo plazo un generador fotovoltaico para asegurar el correcto funcionamiento o identificar posibles efectos de degradación.
Keywords: Sistemas de energía fotovoltaica; Instalaciones fotovoltaicas; Generadores eléctricos--Modelos matemáticos; https://purl.org/pe-repo/ocde/ford#1.03.00